3(x+1)-2(3x+7)=14

Simple and best practice solution for 3(x+1)-2(3x+7)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)-2(3x+7)=14 equation:


Simplifying
3(x + 1) + -2(3x + 7) = 14

Reorder the terms:
3(1 + x) + -2(3x + 7) = 14
(1 * 3 + x * 3) + -2(3x + 7) = 14
(3 + 3x) + -2(3x + 7) = 14

Reorder the terms:
3 + 3x + -2(7 + 3x) = 14
3 + 3x + (7 * -2 + 3x * -2) = 14
3 + 3x + (-14 + -6x) = 14

Reorder the terms:
3 + -14 + 3x + -6x = 14

Combine like terms: 3 + -14 = -11
-11 + 3x + -6x = 14

Combine like terms: 3x + -6x = -3x
-11 + -3x = 14

Solving
-11 + -3x = 14

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + -3x = 14 + 11

Combine like terms: -11 + 11 = 0
0 + -3x = 14 + 11
-3x = 14 + 11

Combine like terms: 14 + 11 = 25
-3x = 25

Divide each side by '-3'.
x = -8.333333333

Simplifying
x = -8.333333333

See similar equations:

| -8.5x-5y+12-3.5x-16= | | x^4+12x^3-8x^2=0 | | -8.5x-5y+12-3.5x= | | x^4+12x^3-45x^2=0 | | 3m+7.5= | | 0=-4t^2+24t | | x^4+7x^3-30x^2=0 | | x^2-10x+23=0 | | 19=(-2x)+4 | | 9-3p=8 | | 2x^2+50x+9=5 | | 4x^2-15x-97=0 | | 0.5x+19.3=x-5.55 | | 2x^2+693=4x | | 0.9x+2.64=-0.5x+0.64 | | x^3+5x^2-10x=0 | | 600x-0.32=400x+0.94 | | 9.7=8x+2.5 | | (4x-1)(x)=18 | | y-2.2=10 | | 4x-26.7=x | | 7(x-1.8)=7.7 | | 8.2y+6.99=-64.35 | | 3x+16=2x+10 | | 72x^4+132x^3-36x^2-24x=0 | | x+3.1=6.4 | | 15=z-14 | | (11x+z)(11x-z)=0 | | m-31=-7 | | 3(x+1)=8(x-2)-16 | | (5a+6)(9a^2-8a-4)=0 | | 400x-0.21=600x+0.89 |

Equations solver categories